Antihyperlipidemic Activity of Ethanol Extract Mindi’s Leaves (Melia azedarach Linn.) in Male Wistar Rats Induced Propiltiouracil - Herlina Herlina; Budi Untari; Indah Solihah; Merie Santia (Science and Technology Indonesia, 2019)
Mindi’s leaves (Melia azedarach Linn.) is an Indonesian medicinal plant that used as traditional medicine. Mindi leaves contains some secondary metabolites which have potency to decreased total cholesterol and LDL level. The study purposed to know antihyperlipidemic effect of ethanol extract of mindi’s leaves (Melia azedarach Linn.) seen from total cholesterol, and LDL in male albino rats. Male wistar albino rats were divided into 5 groups, negative control group (sodium CMC 0.5%), positive control group (simvastatin 0.193 mg/200 gBW), group I (ethanol extract mindi’s leaves with dosage 300 mg/200 gBW), group II (ethanol extract mindi’s leaves with dosage 600 mg/200 gBW), and group III (ethanol extract mindi’s leaves with dosage 1200 mg/200 gBW). The rats were given high-fat supplement and propylthiouracil for 15 days to increase cholesterol, and the extract was given for the next 15 days. Average cholesterol level, LDL, and body weight after induction was 90.28 mg/dL, 31.09 mg/dL, and 222.32 g. The result showed ethanol extract mindi’s leaves could decreased total cholesterol level and LDL level with % decreased in total cholesterol (%PDTC) and % decreased in LDL (%PDLDL) of group I is 37.78% and 35.57%, group II is 45.99% and 40.39%, and for group III is 56.29% and 52.42%. The result showed that ethanol extract of mindi’s leaves has antihyperlipidemic activity and significantly different from negative control (p>0.05). Based on the percentage relation of decreased total cholesterol and LDL levels to dose, then the effective dose 50 (ED50) value of ethanol extract mindi’s leave is 869 mg/200 gBW for total cholesterol and for LDL reduction level is 1086.84 mg/200 gBW